OPTIMIZATION OF COMPUTER-BASED INSTRUCTION (CBI) MEDIA ON STUDENT LEARNING OUTCOMES - Dina Ampera; Veronika Yulisna Sinukaban; Farihah; Yudhistira Anggraini; Ismail Jahidin (International Journal of Innovative Technologies in Social Science, 2026)
Purpose. This study aims to determine the effective use of Computer-Based Instruction (CBI) in identifying the learning outcomes of students of the Fashion Design Education Study Program at Universitas Negeri Medan.. Methods. This research is a quasi-experimental research, with a population of 133 students consisting of 4 classes. The research design uses a pretest and posttest to see the learning outcomes of students in the Fashion Technology course. Findings. The use of CBI learning media in the experimental class showed that the achievement of learning outcomes using CBI learning media is better than using other learning media in students of the Fashion Education Study Research Implications. Integrating learning technology that matches the characteristics of visual and procedural materials can support improved learning quality in vocational education. In addition to providing empirical evidence regarding the effectiveness of CBI in Fashion Design Education, this research also serves as a foundation for the development of more innovative digital learning media to support independent, student-centered learning. Originality. The novelty of this research lies in testing the effectiveness of Computer-Based Instruction (CBI) in learning Fashion Technology in the Fashion Design Education Study Program, which has visual and procedural learning characteristics. This research provides empirical evidence regarding the ability of CBI to support practical learning, improve learning outcomes, and facilitate student independent learning in vocational fashion education.